Birth defect: Findings from Obstetrics & Gynae Department of a tertiary Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Objectives: To determine the frequency and types of birth defect among newborn in Sir Salimullah Medical College Hospital Study Design:  Cross-sectional study.Methods: The study was conducted in Sir Salimullah Medical College Hospital from January- December 2018.  Birth defect identified previously during pregnancy on USG or defect detected at birth at Obstetrics department were included in the study. The study was conducted at Obstetrics department of SSMC MH. All births with gross congenital malformations were noted. All malformations were classified as per ICD 10 classification. The mother of the newborn with congenital malformations was interviewed consecutively using predesigned, pretested questionnaire. The variables included parents age, antenatal registration, antenatal history of drug intake, consanguinity and previous history of malformations. Statistical analysis was done using chi square test.Results: Out of 8912   live births, congenital malformations were observed in 50 cases. The frequency of congenital malformation   was 0.56%. There were 25 males and 23 females and two newborns had ambiguous genitalia. The highest congenital abnormality reported in this study was in the age group between 20-29 years, which was 31(62%), The central nervous system was the most common system involved. Among 50 neonates, 8 neonate had multiple congenital anomalies and 42 babies had isolated malformations.Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 127-131